2022
DOI: 10.1302/2633-1462.38.bjo-2022-0074.r1
|View full text |Cite
|
Sign up to set email alerts
|

Who, if anyone, may benefit from a total hip arthroplasty after a displaced femoral neck fracture?

Abstract: Aims The aim of this study was to explore the functional results in a fitter subgroup of participants in the Hip Fracture Evaluation with Alternatives of Total Hip Arthroplasty versus Hemiarthroplasty (HEALTH) trial to determine whether there was an advantage of total hip arthroplasty (THA) versus hemiarthroplasty (HA) in this population. Methods We performed a post hoc exploratory analysis of a fitter cohort of patients from the HEALTH trial. Participants were aged over 50 years and had sustained a low-energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…34 In particular, the decisionmaking between THA and HA can be improved. 35 As risk factors for PJIs, older age, increased BMI, and a high number of (cardiovascular) comorbidities were evaluated recently. 36,37 This specific group of patients suffers from a modified or weakened immune system and reduced blood flow in the periphery, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…34 In particular, the decisionmaking between THA and HA can be improved. 35 As risk factors for PJIs, older age, increased BMI, and a high number of (cardiovascular) comorbidities were evaluated recently. 36,37 This specific group of patients suffers from a modified or weakened immune system and reduced blood flow in the periphery, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The HEALTH trial found no short-term benefit of THA over HA for patients >50 years with a displaced FNF after a 2-year follow-up [ 28 ]. Not even the youngest (50–70 years) and fittest (ASA grade I or II) patients benefit from a THA with a short-term follow-up of 2 years [ 15 ]. However, the potential benefit of THA is the avoidance of acetabular erosion and worsening hip function with time, which can come into play in younger and active patients with a longer life span.…”
Section: Discussionmentioning
confidence: 99%
“…In most patients current evidence cannot detect any differences of clinical importance between THA and HA approaches [ 15 ]. Notable is the high age cut-off (60 to 70 years) [ 16 , 17 ] in Scandinavia for using IF for displaced FNFs.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence for the optimal treatment remains mixed. [2][3][4][5][6] There is considerable variation in practice patterns between healthcare systems, regions, institutions, and individual surgeons. [7][8][9][10] The purpose of this population-based cross-sectional study was to describe practice variation in the use of THA versus HA for patients aged 60 years and older with femoral neck fracture in Ontario, Canada, and to determine patient, surgeon, and institution factors that predicted treatment with THA.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence for the optimal treatment remains mixed. 2-6 There is considerable variation in practice patterns between healthcare systems, regions, institutions, and individual surgeons. 7-10…”
Section: Introductionmentioning
confidence: 99%